Reducing Pain in Children with Cancer Using A Combination of Benson Relaxation and Peppermint Essential Oil Aromatherapy - Yuli Astuti; Sutiawati, Dewi Nur; Uum Safari (Talenta Publisher, 2024)
Childhood cancer is a chronic disease that often causes significant pain. This pain may result from the disease itself or from procedures necessary for treatment. In addition to pharmacological therapies, non-pharmacological approaches can be utilized to alleviate pain in children with cancer. Benson Relaxation is a non-pharmacological technique that can help reduce pain through deep breathing exercises accompanied by the repetition of positive words aligned with the child's faith. Another non-pharmacological therapy, peppermint oil aromatherapy, is known for its calming properties, which can reduce pain and promote comfort. This study aims to evaluate the combined effect of Benson Relaxation and peppermint oil aromatherapy on pain reduction in children with cancer. Employing a quantitative research design, the study utilized a quasi-experimental approach with a group pre-test and post-test design. The sample consisted of 15 children aged 6 years and older, selected using purposive sampling. Pain levels were measured using a Numeric Rating Scale (NRS) over the course of one week. Data analysis was performed using the Wilcoxon Test, and the results demonstrated a significant effect of the combined intervention in reducing pain levels, with a p-value of 0.001 (p < 0.05). These findings suggest that Benson Relaxation combined with peppermint oil aromatherapy is an effective holistic, non-pharmacological intervention for reducing pain in children with cancer during treatment. It is recommended that this intervention be considered as part of comprehensive care strategies for pediatric cancer patients.